Using BBC Web-Based Learning Courses to Improve Vocational High School (VHS) Students' Speaking Skill - Muhammad Chairil Imran; Sulviana (JURNAL PENDIDIKAN BAHASA DAN BUDAYA, 2022)
The research generally discusses the use of BBC Web-Based Learning Courses to Improve Vocational High School (VHS) students' Speaking Skill. The researchers selected the sample from the population by using total sampling technique. The number of the sample was 45 students. This research was a pre-experimental design with one group pretest and posttest. The group was tested after treatment, the test included pretest and posttest that consisted of 15 items. The result of data analysis showed that there was a significant difference between the mean scores of pretest and posttest. The mean score of posttest was greater than the mean score of pretest. The mean pre-test of the students was 49.30 while the mean post-test was 80.22. It can be concluded that the use of BBC Web-Based Learning Courses Improved Vocational High School (VHS) students' Speaking Skill. It means that there is a significant difference (H1) of the students' Speaking Skill before and after treatment by using BBC Web-Based Learning Courses.